On the importance of Swiss patient data for pharmaceutical R&D in Switzerland - Riccardo Bentele; Rolf Weder (University of Basel, Center of Business and Economics (WWZ), 2024)
Real-world data (RWD) are an increasingly important input into the pharmaceutical R&D process as shown by countries like the USA or Finland. As the availability of and access to Swiss RWD is rather limited, the question arises whether this creates a burden for pharmaceutical R&D in Switzerland. We build on the economics of data and ideas as well as the home-market effect to analyze the importance of local RWD in the three stages of pharmaceutical R&D (pre-clinical, clinical, and post-approval research) as well as in the field of personalized medicine. We find qualitative support for a home-market effect and conclude that there is an urgent need to improve the current RWD situation in Switzerland, from the perspective of both Swiss patients and pharmaceutical R&D in Switzerland.
Keywords: F1; O3; L65; 330; Patient Data; Real-World Data; Pharmaceutical R&D; Data and Innovation; Home-Market Effects; International Trade; Location of R&D